The Study of Human Resources Management in Chinese Banks: The Reasons that Chinese State-Owned Commercial Banks’ Staff Has the Intention to Quit - Xu, Linxiao (2014)
This paper aims to analysis the reasons that state-owned commercial banks’ (SOCBs) staff has the intention to turnover, and try to provide some suggestions to help SOCBs retain their staff. The author decided to study this topic because the author had two months working experience in one of the SOCBs --- Bank of China (BOC). The author finds that the phenomenon of staff’s turnover is not isolated, but it’s widespread and has serious negative impact on these government banks, such as BOC. Through the author’s research, 86.61% respondents in the SOCBs have the intention to turnover to the non-state-owned commercial banks. According to Community Banker (2007), the CEO and president of Cape Cod Cooperative Bank has said that retain their core employees can be a function of the structure of long-term benefit and retain competitive advantage. Thus, it’s necessary to found out the reasons that the staff in SOCBs has the intention to quit. To gain a better understanding of the reasons that SOCBs’ staff has the intention to leave job, a quantitative research study was carried out. The research set out to explore the significant factors that have impact of employees’ intention to quit. The results from this research has demonstrate that the pay satisfaction and job satisfaction was shown a negative relationship with staff’s intention to leave job. More specifically, this study has demonstrated the top seven factors that have impact of intention to quit of both normal staff and middle-level cadres. This research also highlights the shortage of the organisations’ orientation programs. Based on these results, this paper has tried to provide suggestions to the SOCBs.